Alternatives to consumer-oriented food subsidies for achieving nutritional objectives - Kennedy, Eileen T. (International Food Policy Research Institute, 1988)
Malnutrition is a problem associated with poverty. Although all poor people are at risk of having an inadequate food intake, it is usually the maternal and preschooler population that are the most nutritionally vulnerable. As a result, a number of interventions targeted directly on pregnant women and children have been implemented. Examples of approaches aimed at specific individuals include supplementary feeding programs, formulated foods or weaning-food projects, and nutrition education programs.